Optimisation Vs Strategic Stabilisation In the Context of COVID-19 Pandemic - Jacek RUDEWICZ (Communications of International Proceedings, 2021)
The article concerns the reaction of socio-economic systems of different countries and global economic order to the COVID-19 pandemic, observed by the academic environment. In the concept of the paper, the pandemic is considered as an external factor, revealing diagnostic weaknesses of the systems. It emphasises unfavourable impact of broadly defined optimisation. Although the term itself (explained in the text) has positive connotations and forms the basis of rationality and efficiency in management, its weaknesses are revealed in many situations. Examples of unfavourable effects of optimisation onto the human factor in organisations, on value chains and, finally, of their increased susceptibility to crisis related disruptions are collected in the paper. The main objective is preliminary recognition of optimisation disadvantages in different scales and examples. The article is based on first accounts concerning impact of the pandemic onto the economy and entrepreneurs.
Keywords: GVC; Optimisation; Supply Chains; Resilience.